Relationship Between Physical Fitness And Psychological Well-Being On The Quality Of Life Of The Elderly - Prastyawan, Rifky; Suherman, Wawan Sundawan; Nasrulloh, Ahmad (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
This study aims to analyze the relationship between physical fitness and psychological well-being, on the quality of life of the elderly, who are members of gymnastics groups. This cross-sectional study used the World Health Organization QOL short-form questionnaire (WHOQOL-BREF), a senior fitness test, and a psychological well-being scale. The sample consisted of 99 people aged 65 years and members of the elderly exercise community. As a result, no significant relationship was observed. Only three senior fitness test items 6-minute walk, 2-minute step, and sit and reach best explained the overall quality of life in physical, psychological, and environmental domains in the study group. The physical domain and overall quality of life are less significant for all dimensions of psychological well-being. The physical domain correlates only with the environmental mastery dimension, and overall, quality of life correlates better with the two psychological well-being dimensions. In conclusion, psychological well-being is closely related to quality of life, especially in the psychological, social, and environmental domains.